Associations between Smoking, Intrauterine Device Uptake, and Ectopic Pregnancy: A Meta Analysis - Yanuari, Ridha Rossela; Pamungkasari, Eti Poncorini; Widyaningsih, Vitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Ectopic pregnancy is an important cause of maternal morbidity and mortality, estimated to occur in approximately 1-2% of pregnancies worldwide. Smoking and history of using intrauterine devices are risk factors for ectopic pregnancy. This study aims to estimate the magnitude of the relationship between smoking and a history of using intrauterine devices on the incidence of ectopic pregnancy based on a number of previous primary studies. Subjects and Method: This study is a systematic review and meta-analysis. The articles used in this study were obtained from several databases, including: PubMed, Google Scholar, and Science Direct which were published from 2000-2020. The inclusion criteria used are full text articles with Case Control design. The keywords used to search for articles were as follows: smoking AND